2017
DOI: 10.1136/jnnp-2017-316576
|View full text |Cite
|
Sign up to set email alerts
|

Sleep and REM sleep behaviour disorder in Parkinson’s disease with impulse control disorder

Abstract: This large, controlled series of patients with PD with ICDs assessed by v-PSG confirms the association between ICDs and RBD. Increased surveillance of symptoms of ICDs should be recommended in patients with PD with RBD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 40 publications
4
19
0
Order By: Relevance
“…PD-RBD was identified as an independent risk factor in a large cross-sectional study. 8 This finding was then replicated in cohorts with both clinically 44 and polysomnography 7 -diagnosed PD-RBD. Further studies with smaller sample sizes, 4547 aiming to specifically address this question, have failed to show this association.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…PD-RBD was identified as an independent risk factor in a large cross-sectional study. 8 This finding was then replicated in cohorts with both clinically 44 and polysomnography 7 -diagnosed PD-RBD. Further studies with smaller sample sizes, 4547 aiming to specifically address this question, have failed to show this association.…”
Section: Discussionmentioning
confidence: 73%
“…Certain risk factors have been identified, including dopaminergic medication, predominantly dopamine agonists (DAs), along with demographic and disease-specific factors such as the presence of motor complications. In addition, while the presence of REM sleep behavior disorder (RBD) may infer a higher risk of developing PD-ICD, 7,8 it is not known whether RBD itself or whether a particular RBD-PD subtype confers an increase risk. 9…”
mentioning
confidence: 99%
“…Interestingly, patients with ICDs presented with a higher familial history of addictive behaviors (pathological gambling, alcohol abuse), suggesting an important genetic component in this population. In addition, PD patients with ICDs and related behaviors presented more severe nonmotor complications (UPDRS I) and motor complications (UPDRS IV), in accordance with recent studies showing an association of ICDs with dyskinesia and sleep disorders, suggesting common pathogenic mechanisms responsible for the development of severe versions of the disease and emergence of ICDs …”
Section: Discussionmentioning
confidence: 99%
“…Sleep disorders have also been investigated, with some studies finding more sleep impairment and daytime sleepiness in PD patients with ICDs (5, 65). Although some studies that defined sleep disorders through questionnaires found an association with ICDs, more recent studies—including those that have screened sleep disorders through polysomnography exams—have revealed inconsistent results (15, 78, 143, 144). Patients with ICDs may also have more restless leg syndrome (65).…”
Section: Premorbidities and Comorbiditiesmentioning
confidence: 99%